Potential of Chitosan for the Control of Tomato Bacterial Wilt Caused by Ralstonia solanacearum (Smith) Yabuuchi et al - Borines, Lucia M.; Sagarino, Rezel M.; Calamba, Rosario B.; Contioso, Ma. Angelica A.; Jansalin, Jacob Glenn F.; Calibo, Candelario L. (Annals of Tropical Research, 2015)
Bacterial wilt is an important constraint to tomato production. The search for an effective and safe method of managing bacterial wilt is imperative. Chitosan, a deactylated chitin was reported to possess direct antimicrobial property against certain pathogens and is a plant resistance booster. This study was conducted to: evaluate the effectiveness of varying chitosan concentrations and sources against bacterial wilt in vitro and in vivo compare different application methods in bacterial wilt control Varying chitosan concentrations (100, 200, 300, 400 and 500 ppm) immersed/dissolved in water, 1% acetic acid, and streptomycin were evaluated against R. solanacearum in laboratory and pot experiments. Three chitosan sources were also evaluated against the pathogen. Different methods of application were compared. Regardless of source, chitosan in water has no direct antimicrobial activity against R. solanacearum but when dissolved 1% acetic acid, it was able to inhibit the bacteria. Inhibition of chitosan/acetic acid was best at 300 ppm and significantly higher than 1% acetic acid alone indicating that its antimicrobial property was enhanced by the acid. Two hundred ppm chitosan/acetic acid-treated plants delayed the onset of disease and produced the lowest percentage infection, lowest disease severity rating, and highest percentage survival in inoculated tomato. The action of 200 ppm chitosan/acetic acid treatment was due to a dual effect, i.e., antimicrobial and as an elicitor of resistance. All application methods were effective in controlling bacterial wilt but one time root dipping to 200 ppm chitosan/acetic acid before transplanting was enough to protect the plants against the disease.